Safety evaluation of CuminUP60® – A novel curcumin complex. (2022) - Dziwenka, Margitta; Li, Xin; Li, Wenyu; Zong, Jiancheng; Zong, Lei; Wang, Shanglong; Li, Li; Liu, Zimin; Zhang, Zengliang; Wang, Mengyue
Abstract: Curcuma longa L. is one of the most recognized Curcuma species (Sharifi-Rad et al., 2020 [3]). Curcumin, the primary polyphenolic compound found in turmeric has been used for a variety of purposes for centuries. CuminUP60® is a curcumin complex composed of Curcuma longa L. rhizome extract and Poloxamer 407. The results of GLP compliant in vitro and in vivo safety studies conducted with CuminUP60® including a bacterial reverse mutation assay, an in vitro mammalian cell chromosome aberration study and an in vivo micronucleus study are reported here. In addition, a GLP compliant, a single dose toxicity study in Sprague-Dawley rats and a 4-week repeat dose study were also conducted. CuminUP60® was shown to not be mutagenic in a number of in vitro and one in vivo study, the results of which are reported here. A single oral dose of 5000 mg CuminUP60® was well tolerated by male and female Sprague-Dawley rats. The no observed adverse effect level (NOAEL) for CuminUP60® in male and female Sprague-Dawley rats in a 4-week repeat dose study was determined to be 1000 mg/kg bw/day. Highlights: Curcumin is the primary polyphenolic compound found in turmeric. CuminUP60® is a novel curcumin complex. CuminUP60® is nonmutagenic with a NOAEL of 1000 mg/kg bw/day in rats.